Modification, cultural adaptation and validation of burn specific health scale-brief (BSHS-B) for Hindi speaking population. Issue 7 (November 2015) - Mulay, Amit M.; Ahuja, Aarti; Ahuja, Rajeev B.
Highlights BSHS-B was modified by adding 5 items. Questions added were for mobility, itching and economic impact. The new questionnaire was translated to Hindi language. It was delivered by an interview to 20 patients. Results show high validity.